The Zakat Management Legal Conflict of the Prismatic Society in Central Kalimantan - Syaikhu, Syaikhu; Norwili, Norwili; Adawiyah, Rabiatul (Al-Manahij: Jurnal Kajian Hukum Islam, 2022)
The Government established the National Amil Zakat Agency to manage zakat, but the prismatic society tends to be traditionalists in Kapuas Regency are reluctant to pay zakat through it. The study aims to determine the legal conflict in the zakat management of the prismatic society and to find out the causes of the prismatic society's reluctance to pay zakat through the zakat institution. It is descriptive qualitative with an empirical and legislative approach. The results indicate that the legal conflict between the law of zakat management and the prismatic law that applies in society makes the rules overlap and the zakat management for public interests became less optimal. Meanwhile, the causes of why they are reluctant to pay zakat through BAZNAS are the feeling better to give zakat directly to mustahiq, the lack of public understanding of the zakat management benefits by the institution, and the lack of public trust in the institution. There is a need for adjustments to zakat management regulations and providing comprehension that the society and zakat managers must have the awareness to optimize zakat, which is useful for the development of the country and Muslims.